Giving Condolences by Iraqi EFL Teachers: A Gender Perspective - Dr. Mushtaq Abdulrazzaq Abdulzahra (Taez University, 2023)
The dreadful increase in death rates caused by the COVID-19 pandemic, deadly diseases and accidents are all issues that make people give condolences more than ever, and here comes the need to master the speech act of giving condolences to the EFL teachers. However, English teachers have not been called upon to give condolences, particularly in terms of gender. The objective of this study is twofold: (1) To identify the most common strategy by Iraqi EFL teachers and (2) to examine gender variations among these teachers. To this end, a production task was adapted from two related studies. The data were elicited from 39 male and 39 female English language teachers enrolled in the academic year 2020-2021. MS Excel and SPSS were utilized for descriptive and statistical analyses. The study yielded that the females significantly gave more sympathetic, empathetic, suggestive and advising, and combined condolences while the males significantly gave more offering assistance condolences probably based on expressions from their first language.